Label-free detection and identification of single bacteria via terahertz near-field imaging - Wang, Jie; Peng, Liang; Han, Dongxue; Zheng, Teng; Chang, Tianying; Cui, Hong-Liang (Frontiers in Microbiology, 2023)
In recent years, terahertz (THz) imaging has attracted much attention because of its ability to obtain physical and chemical information in a label-free, noninvasive and nonionizing manner. However, the low spatial resolution of traditional THz imaging systems and the weak dielectric response of biological samples hinder the application of this technology in the biomedical field. In this paper, we report a new THz near-field imaging method for a single bacteria, through the coupling effect of nanoscale radius of probe and platinum gold substrate, which greatly enhances THz near-field signal of biological samples. A THz super-resolution image of bacteria has been successfully obtained by strictly controlling the relevant test parameters such as tip parameters and driving amplitude. By analyzing and processing the THz spectral image, the morphology and inner structure of bacteria have been observed. The method has been used to detect and identify Escherichia coli represented by Gram-negative bacteria and Staphylococcus aureus represented by Gram-positive bacteria. This application provides a new label-free, noninvasive and nonionizing testing protocol for the detection of single bacteria.